Evaluation of IGK and IGL molecular gene rearrangements according to the BIOMED-2 protocols for clinical diagnosis of Hodgkin lymphoma. Issue 3 (15th March 2016) - Ghorbian, Saeid; Jahanzad, Issa; Javadi, Gholam Reza; Sakhinia, Ebrahim
Abstract : Background : Although the analysis of molecular clonality rearrangements of the immunoglobulin light chains ( IGK and IGL ) is an alternative approach for diagnosis of B cell non-Hodgkin lymphomas (NHLs) using BIOMED-2 protocols, NHLs have not been extensively confirmed for Hodgkin lymphoma (HL) cases. We evaluated BIOMED-2 protocols in HL cases, which have been suggested previously as gold standard method for molecular clonality analysis on formalin fixed, paraffin-embedded (FFPE) tissue in NHL patients. Methods : We recruited 50 consecutive FFPE tissues of HL samples to evaluate IGK and IGL clonality gene rearrangements using BIOMED-2 and Heteroduplex methods. Results : Our findings revealed a total of 94% (47/50) positive clonality, which consisted of 70% (35/50) for IGK and 44% (22/50) for IGL . In three cases, clonality was not detected in any of the immunoglobulin gene segments. Conclusions : Analysis of clonality gene rearrangements in IGK and IGL genes using BIOMED-2 protocols could be implemented as a valuable method for improving clonality detection rate in HL cases and sensitivity (94%) and accuracy of HL diagnosis similar to that of the NHL samples will be increased.